Partial Isothermal Sections of the Cu-Rich Corner of the Al-Cu-Zn System at 200 and 240 °C - Ngugi, Johnson; Rading, George Odera; Ngobe, Bongani; Forbes, Roy (Springer US, 2019)
Partial isothermal sections of the Cu-rich corner of ternary Al-Cu-Zn system at 200 and 240 C were plotted up to 55 at.% Cu and 85 at.% Zn based on scanning electron microscopy, energy-dispersive x-ray spectroscopy and x-ray diffractometry analyses of ten ternary alloys. Seven phases were observed at both isothermal temperatures, and no new ternary phases were found. The results were compared with previously published works, and the c-phase was confirmed to exist as two phases: c Cu9Al4 and c Cu5Zn8.
Keywords: Alloys; binary system; isothermal section; phase diagram; phase equilibria; ternary phase